Can Sodium Oxybate Mitigate the Symptoms of Schizophrenia? - Mamelak, Mortimer (Current Neuropharmacology, 2026)
Schizophrenia remains a therapeutic challenge. For much of its long history, the physiological basis of its symptoms and clinical presentation remained elusive. However, in recent decades, consistent anatomical and metabolic changes have been documented that can also serve as therapeutic targets. An insult to the developing nervous system in the prenatal or neonatal period appears to set the schizophrenic syndrome in motion by preventing the development of the normal circuit balance between inhibitory and excitatory neurons. In time, a reduction in the volume of frontal and temporal grey matter and a decrease in the density of dendritic spines on pyramidal neurons becomes apparent. These anatomical findings are accompanied by a reduced capacity to synthesize GABA, an increased capacity to synthesize and release dopamine, and an increased level of blood cortisol. Treatment with sodium oxybate (SO) (gammahydroxybutyrate) may make it possible to reverse these pathological features of the schizophrenic syndrome, given SO’s potential to increase neuronal levels of GABA, inhibit dopamine release and reduce blood cortisol levels. SO can also serve as a source of energy to promote the growth of the dendritic arbor on excitatory pyramidal neurons and as an antioxidant to enhance the activity of GABAergic inhibitory neurons. In this way, SO may restore the balance between the excitatory pyramidal neurons and the inhibitory GABAergic neurons in schizophrenia. In a short clinical trial, the use of SO to improve the sleep of patients with chronic schizophrenia led to a significant clinical improvement.
Keywords: sodium oxybate